2021
DOI: 10.3390/ani11041082
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and Dental Status in Packs of Spanish Dogs

Abstract: While periodontal disease (PD) is the most common canine oral pathology, its prevalence varies according to diagnosis methodology, breed, and age. We intended to increase understanding of canine PD by studying dogs that are managed in a specific way: pack dogs in Spain. They received a mixed diet (home-prepared food, commercial dry food, stale bread and bones). Thirty-two conscious individuals from two packs of dogs in Northeastern Spain (30/32 crossbred hunting dogs and 2/32 Siberian Husky; 26 males and 6 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Halitosis is most commonly associated with dental disease ( 5 ), including gingivitis, and increase accordingly. Regarding dental calculus, previous studies have suggested a prevalence of 61–100% ( 1 , 4 , 9 , 31 ). Dental calculus is also an indicator of poor dental hygiene and was reported by 53% of dog owners, but it was detected in almost all three-year-old dogs during the examination, increasing the evidence that dental calculus is under-reported by dog owners.…”
Section: Discussionmentioning
confidence: 99%
“…Halitosis is most commonly associated with dental disease ( 5 ), including gingivitis, and increase accordingly. Regarding dental calculus, previous studies have suggested a prevalence of 61–100% ( 1 , 4 , 9 , 31 ). Dental calculus is also an indicator of poor dental hygiene and was reported by 53% of dog owners, but it was detected in almost all three-year-old dogs during the examination, increasing the evidence that dental calculus is under-reported by dog owners.…”
Section: Discussionmentioning
confidence: 99%